Complete Duplication of Collecting System in a Horseshoe Kidney Presenting with Recurrent Urinary Tract Infections: Report of an Exceedingly Rare Congenital Anomaly and Review of Literature - Majid Mirzazadeh; Kyle A. Richards (The Scientific World Journal)
We report the fifth case in the English literature of a horseshoe kidney with a complete ureteral duplication. Our case is unique in that the previous four cases occurred in the presence of a ureterocele, whereas our patient lacked this anomaly. Further, our patient was managed conservatively, whereas the previous four patients were managed with surgery.